2019
DOI: 10.5194/hess-23-971-2019
|View full text |Cite
|
Sign up to set email alerts
|

Energy states of soil water – a thermodynamic perspective on soil water dynamics and storage-controlled streamflow generation in different landscapes

Abstract: Abstract. The present study confirms that a thermodynamic perspective on soil water is well suited to distinguishing the typical interplay of gravity and capillarity controls on soil water dynamics in different landscapes. To this end, we express the driving matric and gravity potentials by their energetic counterparts and characterize soil water by its free energy state. The latter is the key to defining a new system characteristic determining the possible range of energy states of soil water, reflecting the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…The same leading author Gao et al (2019) further exploited the role surface topography plays when rainfall becomes runoff and used HAND to infer model parameters of a conceptual hydrological model, showing that their developed runoff generation module performed almost as well as fully calibrated models. Finally, Zehe et al (2019) used HAND as a proxy for the gravitational potential for calculating potential energy of soil water and showed that their approach is "well suited to distinguishing the typical interplay of gravity and capillarity controls on soil water dynamics in different landscapes".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same leading author Gao et al (2019) further exploited the role surface topography plays when rainfall becomes runoff and used HAND to infer model parameters of a conceptual hydrological model, showing that their developed runoff generation module performed almost as well as fully calibrated models. Finally, Zehe et al (2019) used HAND as a proxy for the gravitational potential for calculating potential energy of soil water and showed that their approach is "well suited to distinguishing the typical interplay of gravity and capillarity controls on soil water dynamics in different landscapes".…”
Section: Introductionmentioning
confidence: 99%
“…However, a thermodynamic perspective can be much more general and is by no means limited to the explanation of optimal drainage densities. As examples, Zehe et al (2013) showed that a thermodynamic optimum density of macropores maximizing dissipation of free energy during recharge events allowed an acceptable prediction of the rainfall-runoff response of a lower-mesoscale catchment; Hildebrandt et al (2016) used an energy-centered approach to explain how plants extract water from the soil, Zhang and Savenije (2018) showed how salt and fresh water mixing in estuaries can be described in energetic terms, and finally Zehe et al (2019) discussed how an energetic perspective on soil water movement can improve our general understanding of catchment hydrology.…”
Section: Introductionmentioning
confidence: 99%
“…We note, too, that the CTRW framework also simplifies (e.g. Berkowitz et al, 2006Berkowitz et al, , 2016 to specialized subsets of non-Fickian transport behaviour embodied within, for example, multirate mass transfer (Haggerty and Gorelick, 1995) and fractional derivative (Zhang et al, 2009) formulations. It is important to recognize, too, that specification of a pure exponential form for ψ(t), namely ψ(t) = λ exp(−λt), with mean 1/λ, and/or choice of β > 2, reduces the CTRW transport in Eq.…”
Section: Continuous Time Random Walks: Theorymentioning
confidence: 98%
“…More recent applications demonstrated, in line with this asset, new ways to simplify distributed models without lumping, which allowed the successful simulation of the water balance of a 19 km 2 large catchment using a single effective hillslope model (Loritz et al, 2017). The key to this was to respect energy conservation during the aggregation procedure, specifically through derivation of an effective topography that conserved the average distribution of potential energy along the average flow path length to the stream, and through a macro-scale effective soil water retention curve that conserved the relation between the average soil water content and matric potential energy using a set point-scale retention experiments (Jackisch, 2015;Zehe et al, 2019).…”
Section: Bottom-up Modelling Of the Catchment Water Balancementioning
confidence: 99%
“…However, a thermodynamic perspective can be much more general and is by no means limited to the explanation of optimal drainage densities. As examples, Zehe et al (2013) showed that a thermodynamic optimum density of macropores maximizing dissipation of free energy during recharge events allowed an acceptable prediction of the rainfall-runoff response of a lower-mesoscale catchment; Hildebrandt et al (2016) used an energy-centered approach to explain how plants extract water from the soil, Zhang and Savenije (2018) showed how salt and fresh water mixing in estuaries can be described in energetic terms, and finally Zehe et al (2019) discussed how an energetic perspective on soil water movement can improve our general understanding of catchment hydrology.…”
mentioning
confidence: 99%